Isu-Isu Kontemporer dalam Pendidikan dan Pendidikan Guru: Tantangan, Reformasi, dan Arah Masa Depan - Horas Hutabarat (JET (Journal of English Teaching), 2025)
The effectiveness of educational systems is closely tied to the competence and professionalism of teachers. In the field of English Language Teaching (ELT), these demands have become increasingly complex due to rapid technological change, evolving curriculum policies, and growing expectations for inclusive and responsive pedagogy. This article aims to examine key contemporary issues in English language teacher education and to explore how these challenges are reshaping teacher preparation and professional development. Adopting a qualitative narrative literature review by drawing on relevant scholarly works and policy reports to identify major themes influencing ELT teacher education, the findings reveal several persistent challenges, including the integration of digital pedagogy, the preparation of teachers for diverse classrooms, inconsistencies in educational policy, and the ongoing gap between theoretical preparation and classroom realities. They also highlight the need to reconceptualise teacher education as a process of professional formation and to strengthen systemic coherence across different stages of teacher development. The article concludes by suggesting strategic directions for improving ELT teacher education, emphasizing the importance of integrated training systems, sustained professional learning, and context-responsive policy frameworks.